Effects of xylanase on optical properties of bagasse kraft pulp in ECF bleaching - Hossein Resalti (Regional Information Center for Science and Technology (RICeST), 2009)
The effect of using commercial xylanase enzyme in prebleaching of bagasse kraft pulp was investigated. Xylanase enzyme from Trichoderma viride was added to pulp at various doses of 10, 25 and 50 IU/g pulp for reaction time 2h and then the enzyme treated pulp was bleached in ADED sequences (Acid sulfuric +Dioxide chlorine 4, 6, 8, 10% + Alkaline extraction + Dioxide chlorine 2% as available chlorine). The results have shown that with increased dioxide chlorine in D1 bleaching sequence, final brightness of bleached pulp was increased significantly (P